Nanophenomena at Surfaces Fundamentals of Exotic Condensed Matter Properties - Michailov, Michail (Springer Series in Surface Sciences,, 2011)
This book presents the state of the art in nanoscale surface physics. It outlines contemporary trends in the field covering a wide range of topical areas: atomic structure of surfaces and interfaces, molecular films and polymer adsorption, biologically inspired nanophysics, surface design and pattern formation, and computer modeling of interfacial phenomena. Bridging "classical" and "nano" concepts, the present volume brings attention to the physical background of exotic condensed-matter properties. The book is devoted to Iwan Stranski and Rostislaw Kaischew, remarkable scientists, who played a crucial role in setting up the theoretical fundamentals of nucleation and crystal growth phenomena in the last century.